When will an unethical follower receive poor performance ratings? It depends on the leader's moral characteristics. Issue 5 (4th July 2022) - Zhang, Guanglei; Mao, Jianghua; Hong, Beier
ABSTRACT: Leaders have been thought to play a vital role in influencing employees' unethical behavior. However, what happens to leaders and followers in the aftermath of unethical conduct has received little attention in the literature. Drawing from the correspondent inference theory, we examine the conditions under which leaders attribute their followers' unethical behavior to poor moral character and eventually assign them low performance ratings. Through a two-wave research design and data from 290 matched employee–leader dyads, we found that a leader is more likely to infer that a follower who has engaged in unethical behavior is of poor moral character when the leader has a higher moral identity, and the leader will impose lower performance ratings on this follower when the leader prefers lower moral decoupling.